POSITIP 880: Installation Instructions - Heidenhain (Heidenhain, 2008)
REF The POSITIP 880 is an advanced digital readout system for performing up to 6 axes measurements at very high levels of precision and accuracy. This product is designed for indoor use only. The POSITIP 880 components shall only be installed as described in these instructions. Mounting, installation and maintenance are to be performed by qualified personnel only. Reference-mark evaluation for distance-coded or single reference marks. Distance-to-go mode, nominal position input (absolute or incremental). Scaling factor. Contour monitoring with magnify function. Any axis combinations. HELP: On-screen operating instructions. INFO: Stopwatch, pocket calculator, cutting data calculator (for milling), taper calculator (for turning). For milling/drilling